Behind the Laughter: The Simpsons and Critical Media Literacy (2023)
ABSTRACT: This action research study was conducted at a public institution in Medellín with 30 ninth graders between 14 and 18 years old. It was aimed at exploring the effectiveness of using The Simpsons as a pedagogical tool to foster the students’ Critical Media Literacy. Data were collected through a diagnostic questionnaire for inquiring about their habits, beliefs and attitudes regarding mass media and the way they navigate through the information they receive from them; a research journal in which I consigned descriptions and reflections of the implementation; a focus group with eight students selected based on their active participation in the activities and an interview with the CT in order to gather information about their perceptions and opinions regarding the project; and the students’ final products which consisted of magazine entries about their opinions on social issues. Data analysis showed that The Simpsons proved to be a useful tool that helped the students develop critical awareness in terms of the recognition of the influence of media and the emergence of connections between the show and their own lives. It also showed that they developed skills for the analysis and production of media messages through the examination of their authorship, format, audience, content and purpose. Further research could focus on the application of the Empowerment Spiral to a single media product in more depth.